"Overlapping Memberships": Interactive Multicultural Theory Meets Chalcedonian Christology. (September 2014) - Hesslein, Kayko Driedger
Abstract Chalcedonian Christology defines the relationship between the two natures of Christ as "truly God and truly human" but does not explain how the radically different natures interact with one another. Multicultural theory's model of interactive pluralism proposes that differences engage through "overlapping memberships." Applying this model to the incarnation pushes beyond the limits of Chalcedon to suggest a Christology in which both immanence and transcendence mutually and equally constitute the one person of Christ.